Long-term drug administration in the adult zebrafish using oral gavage for cancer preclinical studies - Michelle Dang; Rachel E. Henderson; Levi A. Garraway; Leonard I. Zon (The Company of Biologists, 2016)
Zebrafish are a major model for chemical genetics, and most studies use embryos when investigating small molecules that cause interesting phenotypes or that can rescue disease models. Limited studies have dosed adults with small molecules by means of water-borne exposure or injection techniques. Challenges in the form of drug delivery-related trauma and anesthesia-related toxicity have excluded the adult zebrafish from long-term drug efficacy studies. Here, we introduce a novel anesthetic combination of MS-222 and isoflurane to an oral gavage technique for a non-toxic, non-invasive and long-term drug administration platform. As a proof of principle, we established drug efficacy of the FDA-approved BRAFV600E inhibitor, Vemurafenib, in adult zebrafish harboring BRAFV600E melanoma tumors. In the model, adult casper zebrafish intraperitoneally transplanted with a zebrafish melanoma cell line (ZMEL1) and exposed to daily sub-lethal dosing at 100 mg/kg of Vemurafenib for 2 weeks via oral gavage resulted in an average 65% decrease in tumor burden and a 15% mortality rate. In contrast, Vemurafenib-resistant ZMEL1 cell lines, generated in culture from low-dose drug exposure for 4 months, did not respond to the oral gavage treatment regimen. Similarly, this drug treatment regimen can be applied for treatment of primary melanoma tumors in the zebrafish. Taken together, we developed an effective long-term drug treatment system that will allow the adult zebrafish to be used to identify more effective anti-melanoma combination therapies and opens up possibilities for treating adult models of other diseases.